PENGEMBANGAN E-MODUL BERBASIS MOODLE PADA MATERI HIDROKARBON - Jimmi Copriady; Siti Nurjannah Iswandari; Asmadi M Noer; Sri Wilda Albeta (EDUSAINS, 2020)
DEVELOPMENT OF E-MODUL BASED ON MOODLE IN HYDROCARBON TOPICAbstractThis study aims to develop e-module with Moodle applications on hydrocarbon materials. This e-module with Moodle application has several advantages, namely learning is more exciting, and learning remotely can be done where educators can still control learning, assessment and giving badges to students who succeed in being the best. This Moodle-based e-module also has discussion forums, quizzes and CBT-based exercises, and there is a feedback page and has an access-right restriction security feature where unregistered users cannot open the e-module. This research method is development research (Research and Development, R & D) with the ADDIE model development model with the instrument of data collection is the validation sheet and questionnaire of respondents. The data analysis technique is by calculating the percentage score of the validation assessment and user response. The results showed that the Moodle-based e-module developed fulfilled very valid criteria from aspects of visual communication, learning design, content, and ease of use with a score of 90.23% in terms of material and 95.67% in terms of media. The results of the test responses of students and teachers each scored 91.67% and 93.45%.. AbstrakPenelitian ini bertujuan untuk mengembangkan bahan ajar e-modul dengan aplikasi Moodle pada materi hidrokarbon. E-modul dengan aplikasi Moodle ini memiliki beberapa kelebihan yakni pembelajaran lebih menarik dan dapat dilakukan dengan jarak jauh dimana pendidik masih dapat mengontrol kegiatan pembelajaran, penilaian dan memberikan lencana bagi peserta didik yang berhasil menjadi yang terbaik, terdapat forum diskusi, kuis dan latihan berbasis CBT serta terdapat laman feedback dan memiliki fitur keamanan pembatasan hak akses dimana pengguna yang tidak terdaftar tidak dapat membuka e-modul. Penelitian ini merupakan penelitian pengembangan dengan model pengembangan model ADDIE. Instrumen penelitian berupa lembar validasi dan kuisioner responden. Teknik analisis data yaitu dengan cara menghitung skor persentase penilaian validasi dan respon pengguna. Hasil penelitian menunjukkan bahwa e-modul berbasis Moodle yang dikembangkan memenuhi kriteria sangat valid dari aspek komunikasi visual, desain pembelajaran, isi, dan kemudahan penggunaan dengan skor 90,23% dari segi materi dan 95,67% dari segi media. Hasil uji respon peserta didik dan guru masing-masing memperoleh skor 91,67% dan 93,45%.